Cardiac MRI in Fabry disease - Umer, Muhammad; Kalra, Dinesh K. (Frontiers in Cardiovascular Medicine, 2023)
Fabry disease is a rare, progressive X-linked inherited disorder of glycosphingolipid metabolism due to a deficiency of α-galactosidase A enzyme. It leads to the accumulation of globotriaosylceramide within lysosomes of multiple organs, predominantly the vascular, renal, cardiac, and nervous systems. Fabry cardiomyopathy is characterized by increased left ventricular wall thickness/mass, functional abnormalities, valvular heart disease, arrhythmias, and heart failure. Early diagnosis and treatment are critical to avoid cardiac or renal complications that can significantly reduce life expectancy in untreated FD. This review will focus on the role of cardiovascular magnetic resonance imaging in the diagnosis, clinical decision-making, and monitoring of treatment efficacy.